Aging‐induced optical anisotropy in thermally grown thin ZnTPP films on Si. Issue 9 (29th May 2013) - Kate, Stephan Peter; Pop, Simona; Esser, Norbert; Rappich, Jörg; Zhang, Xin; Hinrichs, Karsten
<x xml:space="preserve">Abstract</x> We present reflection anisotropy spectroscopy (RAS) as a powerful optical technique for degradation studies of structurally changing thin organic films, here the case of porphyrin films. The measured optical anisotropy of a thin (d = 16 nm) ZnTPP (Zinc tetraphenylporphyrin) film grown by thermal evaporation on silicon using reflectance anisotropy spectroscopy was studied before and after aging in ambient conditions. The observed absorption features, also found by standard transmission spectroscopy, are correlated with the π–π* electronic transitions of the Q and Soret bands of the molecule. Simulation of RAS spectra revealed blue‐shifted resonances, which are in agreement with a preferential face‐to‐face (stacking) arrangement of the ZnTPP molecules. The findings are in agreement with atomic force microscopy studies of the surface morphology showing with aging a transition from a closed film to separated aggregates.